A modified algorithm for species specific motif discovery - Syed Abdullah, Sharifah Lailee; Harun, Hazaruddin; Taib, Mohd Nasir (2010)
Motif discovery can be used to categorize unknown DNA sequences into their corresponding families. For this study, PSO was modified for discovering motif.The modified Linear-PSO is chosen even though it is a slower because linear search is not a choice but a necessary criteria for identifying motif of pig (Sus Scrofa).Pig motif identification is a critical for halal authentication.The modified Linear-PSO algorithm used linear number for population initializing and next position updating.For each cycle, only a particle called ‘target motif’ was selected and compared with other DNA sequences for fitness calculation. Motif discovered can be used as a standard motif for species identification. Experimental results show that the modified algorithm is able to identify motifs as expected. This study showed that a slower algorithm is still needed and has value based on how critical the problem is.